Penggunaan Rasio Keuangan Camel Untuk Memprediksi Kepailitan Dengan Discriminant Analysis Models Z Score: Studi Kasus Pada Bank Perkreditan Rakyat di Indonesia - Hesti Budiwati; Ainun Jariah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2014)
The challenge of the banking sector in the future will be more severe, most of which are perceived as a failure of risk management in managing risk can lead to bankruptcy. “Bank Perkreditan Rakyat” became the object of this study because it has specific operational characteristics that allow it to reach and serve small and micro businesses and focus its services according to the needs of the community. The purpose of this study is to obtain empirical evidence about the differences in financial ratios simultan and partially eously CAMEL which is significant between bankrupt and not bankrupt banks. This research includes survey research. It is explanatory and predictive. The sample involves study sample totaled 43 BPR consisting of 6 BPR bankrupt banks and 37 BPR in the bank classified as a not bankrupt bank determined based on purposive sampling technique. The analytical tool used is discriminated analysis models used for Z score. The results showed that simultaneous CAMEL 7 financial ratios consisting of CAR, NPL, ROA, ROE, ROA, NIM and LDR have significant differences between banks bankrupt and not bankrupt, while partial insignificant is the ratio of NIM. ROA as an aspect ratio of earnings which become dominant variable in distinguishing banks bankrupt and not bankrupt. Simultaneously 7 (seven) CAMEL financial ratios used to predict bankrupt and not bankrupt influence the bankrupt of “Bank Perkreditan Rakyat” for 96.04%, while the remaining 3.96% is influenced by other factors outside the model. Other results obtained from this research is by using a model cut-off point, the discriminated function generated by CAMEL financial ratios to predict the bank is able to distinguish who is in financial difficulty.